2022
DOI: 10.1538/expanim.21-0143
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oxidative damage parameters by carvacrol on methanol-induced liver injury in rats

Abstract: The methanol metabolite that causes hepatotoxicity is formic acid, generating reactive oxygen radical formation and cell damage. Carvacrol is an antioxidant monoterpenic phenol produced from Thymus vulgaris. This study aimed to investigate the effects of carvacrol on methanolinduced oxidative liver damage in rats. Eighteen rats were divided into three groups.Methotrexate was administered orally for 7 days to methotrexate+methanol (MTM) and methotrexate+methanol+carvacrol (MMC) groups. Methotrexate was given be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…MDA is one of the most frequently researched, reliable, and popular products of oxidative stress and LPO. An increase in MDA is associated with biological damage, and a decrease is associated with protection [23][24][25]. In the current study, the increase in the amount of MDA in the gastric tissue of animals administered indomethacin is consistent with the literature and indicates oxidative stress [21,26].…”
Section: Discussionsupporting
confidence: 90%
“…MDA is one of the most frequently researched, reliable, and popular products of oxidative stress and LPO. An increase in MDA is associated with biological damage, and a decrease is associated with protection [23][24][25]. In the current study, the increase in the amount of MDA in the gastric tissue of animals administered indomethacin is consistent with the literature and indicates oxidative stress [21,26].…”
Section: Discussionsupporting
confidence: 90%
“…36 In addition, it was shown that increased inflammatory cells and pro-inflammatory mediators were associated with ROS production. 37…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in the acrylamide group, antioxidant systems are insufficient to neutralize ROS. Gursul et al reported that carvacrol protected the liver tissue from oxidative damage by preventing the decrease in tGSH and TAS ( Gursul et al, 2022 ). In another study, it was reported that carvacrol protects liver tissue against oxidative stress ( Imtara et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%